Historic Development of Peunayong Area Banda Aceh Based on Archived Maps - Jasman, Jasman; Agustina, Agustina; Achmad, Ashfa (Ridwan Institute, 2025)
The Peunayong area holds significant historical value in the development of Banda Aceh. Initially, this area functioned as a trade center before transforming into a Chinatown during the Dutch colonial era, reflecting its cultural diversity. After the 2004 tsunami, Peunayong was designated as a historic district due to the numerous late 19th to 20th-century buildings featuring a blend of Chinese, European, and local architectural styles. However, this cultural heritage is threatened by rapid urban development, necessitating a long-term management policy. This study aims to identify the development of Peunayong across the sultanate, colonial, and independence periods using a qualitative descriptive method. The research utilizes six area maps from 1646 to 2023, representing the evolution of each period. The analysis focuses on land use, circulation systems, as well as building mass and form. The findings reveal both changes and enduring aspects, along with their dynamics, which can serve as a foundation for conservation planning. The maps indicate that Peunayong has maintained clear physical boundaries since early on. The persistent land-use aspects include ports, military functions, commercial areas, and residential zones. The circulation system has undergone significant changes, transitioning from a water-based to a land-based system, while building mass and form have gradually densified, shaping Peunayong's present-day character. Certain elements identified in the old maps can be strategically reinforced or reintroduced for historical education and to strengthen the area's identity, such as revitalizing residential and water transportation functions and interpreting the narratives of the railway line and Gadjah Island as inspirations for planning Peunayong’s historic district.